Numerical modelling of the flow around rowing oar blades - Coppel, A.; Gardner, T.; Caplan, N.; Hargreaves, D. (The Engineering of sport 7, Volume 1, 2008)
Recent experimental studies have presented the lift and drag coefficients for a range of oar blades. However, these studies were not able to provide insight into the mechanisms of lift and drag generation. The aims of this study, therefore, were to model the flow around an oar blade using computational fluid dynamics (CFD), and to validate this model against experimental data.